Utility of Clinical and Radiological Markers in Diagnosing Cerebral Tuberculoma and Neurocysticercosis - Patra, Chandrakanta; Paul, Shabeer Ahmad; Mondal, Gouranga Prosad; Bhattacharyya, Ramesh; Ghosh, Kartik Chandra (Indian Journal of Neurosurgery, 2023)
Background Ring-enhancing lesion is one of the most common radiological findings in a spectrum of diseases affecting the central nervous system (CNS) including infectious, inflammatory, demyelinating, and neoplastic pathologies.Objective The aim of this study was to analyze the clinical and radiological parameters of pathologies presenting as ring-enhancing lesions in the brain, especially tuberculoma and neurocysticercosis.Materials and Methods In this study, 58 patients with ring-enhancing lesions on brain magnetic resonance imaging (MRI) were recruited. Cases were studied for different clinical and radiological variables. Data were analyzed using SPSS 20 version.Results Tuberculoma is the most common pathology accounting for ring-enhancing lesions in the brain, followed by neurocysticercosis. Seizures were present in the majority of cases, with focal onset seizures being more common than generalized seizures. Multiple ring-enhancing lesions were present in the majority of cases, with the cerebral cortex being the most frequently involved site. On T2 fluid-attenuated inversion recovery (FLAIR) sequence, 2/3rds of the neurocysticercosis cases showed full suppression, whereas only 1/10th of tuberculoma cases showed full suppression. On diffusion-weighted imaging (DWI), a minority of neurocysticercosis cases showed diffusion restriction, while more than one-fifth of tuberculoma cases showed diffusion restriction. MR spectroscopy (MRS) results showed that a normal lipid lactate peak was observed in the majority of neurocysticercosis cases, whereas more than half of tuberculoma cases had a high lipid lactate peak. The choline-to-creatine ratio (Chol/Cre ratio) was less than 1.2 in one-third of neurocysticercosis cases and between 1.2 and 2.0 in two-thirds of the cases. In contrast, more than half of tuberculoma cases showed a Chol/Cre ratio between 1.2 and 2.0.Conclusion Tuberculoma and NCC are the two most common causes of ring-enhancing lesions in developing world. Radiological characteristics like FLAIR suppression and diffusion restriction on MRI and Chol/Cre ratio and lipid peak on MRS can substantiate the clinical parameters in distinguishing the two pathologies to a good extent.
Keywords: ring-enhancing lesions; tuberculoma; neurocysticercosis